2021
DOI: 10.3390/ijms22189780
|View full text |Cite
|
Sign up to set email alerts
|

Alisporivir Improves Mitochondrial Function in Skeletal Muscle of mdx Mice but Suppresses Mitochondrial Dynamics and Biogenesis

Abstract: Mitigation of calcium-dependent destruction of skeletal muscle mitochondria is considered as a promising adjunctive therapy in Duchenne muscular dystrophy (DMD). In this work, we study the effect of intraperitoneal administration of a non-immunosuppressive inhibitor of calcium-dependent mitochondrial permeability transition (MPT) pore alisporivir on the state of skeletal muscles and the functioning of mitochondria in dystrophin-deficient mdx mice. We show that treatment with alisporivir reduces inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…(2) the therapy of downstream pathological changes, such as transplantation of muscular stem cells, corticosteroids (prednisolone or deflazacort) with highly effective in therapy of concomitant destructive processes (namely inflammation) and an improvement in calcium homeostasis, leading to a decrease in oxidative stress in muscle tissue, and in mitochondrial function and biogenesis [45][46][47][48][49][50][51][52][53][54][55] (Figure 1). Currently, gene editing is attracting attention as a therapeutic strategy for DMD because of the restoration of the dystrophin reading frame in more than 40% of all patients with DMD [56][57][58][59][60][61][62][63].…”
Section: Therapy Strategy Of Dmdmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) the therapy of downstream pathological changes, such as transplantation of muscular stem cells, corticosteroids (prednisolone or deflazacort) with highly effective in therapy of concomitant destructive processes (namely inflammation) and an improvement in calcium homeostasis, leading to a decrease in oxidative stress in muscle tissue, and in mitochondrial function and biogenesis [45][46][47][48][49][50][51][52][53][54][55] (Figure 1). Currently, gene editing is attracting attention as a therapeutic strategy for DMD because of the restoration of the dystrophin reading frame in more than 40% of all patients with DMD [56][57][58][59][60][61][62][63].…”
Section: Therapy Strategy Of Dmdmentioning
confidence: 99%
“…(dystriphin-targeted therapies), such as adeno-associated virus (AAV)-mediated micro/minidystrophin gene delivery, synthetic antisense oligonucleotides for exon skipping, nonsense readthrough, CRISPR-Cas9 (clustered regularly interspaced short palindromic repeat-CRISPR-associated protein 9)-mediated genome editing, protein replacement therapies, and primarily utropin; (2) the therapy of downstream pathological changes, such as transplantation of muscular stem cells, corticosteroids (prednisolone or deflazacort) with highly effective in therapy of concomitant destructive processes (namely inflammation) and an improvement in calcium homeostasis, leading to a decrease in oxidative stress in muscle tissue, and in mitochondrial function and biogenesis [45][46][47][48][49][50][51][52][53][54][55] (Figure 1). Currently, gene editing is attracting attention as a therapeutic strategy for DMD because of the restoration of the dystrophin reading frame in more than 40% of all patients with DMD [56][57][58][59][60][61][62][63].…”
Section: Therapy Strategy Of Dmdmentioning
confidence: 99%
“…Usually, the CRC is quantified in isolated mitochondria spectrophotometrically (light scattering) or using different Ca 2+ -sensitive dyes. For example, along with Ca 2+ -sensitive fluorescent dyes, arsenazo III, a non-membrane-permeant Ca 2+ -sensitive dye [101][102][103][104], and Ca 2+ -sensitive electrodes [104,105] have been used to measure Ca 2+ release/PTP opening in isolated mitochondria. Notably, the estimation of the CRC/PTP opening in isolated mitochondria has several disadvantages [6,49,50].…”
Section: Mitochondrial Swelling and Calcium Retention Capacitymentioning
confidence: 99%
“…The mitigation of the calcium-dependent destruction of skeletal muscle mitochondria is considered to be a promising adjunctive therapy in Duchenne muscular dystrophy (DMD). The study by Dubinin et al investigated the effect of the intraperitoneal administration of alisporivir, a nonimmunosuppressive inhibitor of the calcium-dependent mitochondrial permeability transition (MPT) pore, on the state of skeletal muscles and the functioning of mitochondria in dystrophin-deficient mdx mice [ 8 ]. The authors showed that treatment with alisporivir reduces inflammation, thus improving muscle function in mdx mice.…”
mentioning
confidence: 99%
“…The authors showed that treatment with alisporivir reduces inflammation, thus improving muscle function in mdx mice. These effects of alisporivir were associated with recovery in the ultrastructural alterations of mitochondria; the normalization of respiration and oxidative phosphorylation and a decrease in lipid peroxidation, due to suppression of MPT pore opening; and an improvement in calcium homeostasis [ 8 ]. The MPT pore targeting approach may be used as an effective adjunctive strategy in the treatment of DMD.…”
mentioning
confidence: 99%